The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1149/2.0971510jes
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion and Passivation of High Nitrogen Face-Centered-Cubic Phase Formed on AISI 304L Austenitic Stainless Steel in Borate Buffer Solution

Abstract: The corrosion behavior of a high nitrogen face-centered-cubic (f.c.c.) phase (γ N ) formed on plasma-based low-energy nitrogen ion implanted AISI 304L austenitic stainless steel in a borate buffer solution with a pH value of 8.4 was investigated by using anodic polarization, electrochemical impedance spectroscopy, Mott-Schottky analysis and Auger electron spectroscopy/x-ray photoelectron spectroscopy. Compared with original austenitic stainless steel, the γ N phase layer on austenitic stainless steel possessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Wang et al reported similar results with austenitic stainless steels: the passive current density of the plasma nitrided stainless steel in a borate buffer solution at pH 8.4 was reported to be one tenth that of untreated stainless steel. 34 The difference between the passive current density of the untreated carbon steel and the nitrogen solid solution layer in the buffer solution at pH 8.45 suggests that, besides alkalization (OH − ions), the other dissolution products of interstitial nitrogen, such as NO 3 − ions, had an effect on the anodic polarization behavior of the nitrogen solid solution layer.…”
Section: Resultsmentioning
confidence: 99%
“…Wang et al reported similar results with austenitic stainless steels: the passive current density of the plasma nitrided stainless steel in a borate buffer solution at pH 8.4 was reported to be one tenth that of untreated stainless steel. 34 The difference between the passive current density of the untreated carbon steel and the nitrogen solid solution layer in the buffer solution at pH 8.45 suggests that, besides alkalization (OH − ions), the other dissolution products of interstitial nitrogen, such as NO 3 − ions, had an effect on the anodic polarization behavior of the nitrogen solid solution layer.…”
Section: Resultsmentioning
confidence: 99%
“…It has been hypothesized that the lower donor density in the outer n-type iron oxide/hydroxide region decreases the pitting nucleation ability, hindering the chloride-ion adsorption [225]. A decrease of donor and acceptor densities and of the corresponding flat band potential has also been observed for nitrided AISI 304L tested in borate buffer solution at pH 8.4 [242].…”
Section: Semiconducting Properties Of the Passive Filmmentioning
confidence: 97%
“…The MS plots were explained as a p-type inner oxide layer and an n-type outer oxide layer based on the composition difference of the bilayered film in a microstructure respect. 11,19,20 This interpretation is different from the KP of passive Cr. For the KPs herein, it was concluded that they were closely related to the variation of the dc and that near where the second or first derivatives of I(E) were zero, the KPs usually occurred.…”
Section: Resultsmentioning
confidence: 82%
“…A KP is not common for an ideal semiconductor. However, this feature also commonly appears in the MS plots of some thin passive films, including those on iron, 5,6 nickel, 7,8 stainless steels, [9][10][11] and Ni-Cr-Mo alloys. [12][13][14] The KP of passive Cr has been attributed to the film oxidation of Cr 3+ to Cr 6+ .…”
mentioning
confidence: 99%